Implementation of the Military Law on Military Members Involved in the Crime of Desertion - Prakamto, Rudy Dwi; Prasetyo, Teguh; Bungin, Sator Sapan (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
Desertion is a military crime involving members of the Indonesian National Armed Forces (TNI) leaving their duties or military obligations without proper authorization from their superiors. Desertion has serious implications for military discipline, cohesion, and operational efficiency, and it can threaten national defense. The legal enforcement of desertion offenses is regulated under the Military Penal Code (KUHPM), particularly Articles 87 and 88. The process of handling desertion cases involves investigation by the Military Police (POM), investigation by military investigators, and trial by military courts that issue rulings according to the applicable laws. The penalties imposed vary, ranging from imprisonment, demotion, dishonorable discharge, and even the death penalty during wartime.This study aims to explore in-depth the implementation of military law on individuals who commit desertion and to analyze the factors causing desertion. These factors include personal issues, psychological pressure, and unfavorable working environments. The study employs a normative juridical method, with an approach focused on relevant regulations and military court case studies concerning desertion offenses. The findings show that the application of military law to desertion is a crucial effort in maintaining the stability, discipline, and integrity of the TNI. However, there are several challenges in enforcing the law, such as internal and external factors affecting military personnel. In the relationship between the Military Penal Code (KUHPM) and the Criminal Code (KUHP), both are complementary, where general crimes are regulated by the Criminal Code (KUHP), while offenses related to military duties are governed by the Military Penal Code (KUHPM). This study recommends strengthening law enforcement and discipline training to minimize desertion within the military.